2020
DOI: 10.1002/csc2.20062
|View full text |Cite
|
Sign up to set email alerts
|

Temporal water use by two maize lines differing in leaf osmotic potential

Abstract: Two lines of maize which had different levels of expressions of leaf osmotic potential (OP) under water-deficit conditions in the field were previously found to differ in leaf area duration and water extraction at soil depths greater than 0.80 m. In the current study, the hypothesis was explored that the difference in leaf OP between the two lines was associated with differences in transpiration rate which in turn had a major effect on the temporal dynamics of soil water use. The line with the lowest (most neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…It was found that the near-isoline with the lower OP had greater leaf area duration, water extraction at soil depths greater than 0.80 m, and grain yield. In controlled-environment studies, Beseli et al [8] found that the maize near-isoline with the lower (more negative) osmotic potential (LOP) in the early stages of the soil drying cycle had the greatest transpiration rate and delayed wilting, which was consistent with the original field observations. Visual wilting was observed in the LOP plants 4 days after wilting developed in the high osmotic potential (HOP) near-isoline.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…It was found that the near-isoline with the lower OP had greater leaf area duration, water extraction at soil depths greater than 0.80 m, and grain yield. In controlled-environment studies, Beseli et al [8] found that the maize near-isoline with the lower (more negative) osmotic potential (LOP) in the early stages of the soil drying cycle had the greatest transpiration rate and delayed wilting, which was consistent with the original field observations. Visual wilting was observed in the LOP plants 4 days after wilting developed in the high osmotic potential (HOP) near-isoline.…”
Section: Introductionsupporting
confidence: 55%
“…Limiting transpiration by partial stomatal closure, especially early in the crop growing season and high VPD conditions, will allow plants to conserve soil water for use when drought may 2 of 13 develop. This limited-transpiration (TR lim ) trait in response to high VPD has been observed in the genotypes of several crop species [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The osmotic adjustment in the leaves of the hybrids examined here was closely correlated with end-of-season grain production, predawn water potential, and marginally with water transport and photosynthesis, again suggesting a logical network of traits leading to improved performance (Figures 1 and 3, "wet"). Although osmotic adjustment is a known beneficial drought response in vascular species, including maize (Ashwini et al 2019;Beseli et al 2019), our results suggest that it might serve as a more effective breeding target if other closely aligned traits, namely K leaf and A N can also be targeted.…”
Section: Resultsmentioning
confidence: 87%